Graph Staining Application against Chemical Storage - Muhlisatul Mahmudah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
Graf G = (V, E), where V is the set of points and E is the set of sides. Interesting application of a graph, one of which is graph coloring (graph coloring). There are three kinds of coloring that are point coloring, edge coloring, and region coloring. In this paper will be studied dye staining. Point coloring is to color the dots of a graph so that no two neighboring dots have the same color. The minimum number of colors that can be used to color graph is expressed by chromatic numbers. Currently a lot of applications from graph coloring, one of which is the storage of chemicals. In the storage of chemicals required a good arrangement, this is due to the influence of chemicals with each other if stored simultaneously.The main focus of this paper is to determine the chromatic number in graph o and the application scheme of dye graph coloring.Keywords: graph coloring, point coloring, edge coloring and region coloring